Gradient multilayer nano Ti (C, N)-based metal ceramic and preparation method

Through the combination of gradient multi-layer nanostructures and graphene nanosheets, the problem of insufficient fracture strength and toughness of Ti(C,N)-based metal cermet is solved, and the hardness and fracture toughness of the material are taken into account, extending the service life and improving the Application performance.

CN119464818APending Publication Date: 2025-02-18HENAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411452839.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Ti(C,N)-based cermet has low fracture strength and toughness during processing, resulting in microcracks easily occur inside the material, reducing service life and hindering its widespread application.

Method used

The preparation method of gradient multi-layer nano-Ti(C,N)-based cermet is adopted to control the different mass proportions of molybdenum carbide in the surface and core layers to form a hard phase enrichment area and a bond phase enrichment area, combined with graphene The addition of nanosheets improves the hardness and fracture toughness of the material.

Benefits of technology

It realizes Ti(C,N)-based cermet with both hardness and fracture toughness, which weakens stress concentration, extends the service life of the material, and improves its application performance in cutting tools and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464818A_ABST
    Figure CN119464818A_ABST
Patent Text Reader

Abstract

A gradient multilayer nano Ti (C, N)-based metal ceramic and a preparation method thereof relate to the field of powder metallurgy, and the method comprises the following steps: S1, mixing 64.9% by mass of titanium carbonitride, 23% by mass of tungsten carbide, 8% by mass of cobalt, 4% by mass of molybdenum carbide and 0.1% by mass of graphene nanosheets to obtain mixed powder I; mixing 60.9% of titanium carbonitride, 23% of tungsten carbide, 8% of cobalt, 8% of molybdenum carbide and 0.1% of graphene nanosheets to obtain mixed powder II; and S2, the mixed powder I and the mixed powder II are added into a mold layer by layer, three layers of mixed powder with the surface layer being the mixed powder II layer and the core layer being the mixed powder I layer are obtained, spark plasma sintering is carried out, and the gradient multi-layer nano Ti (C, N)-based metal ceramic is obtained. According to the Ti (C, N)-based metal ceramic and the preparation method thereof, different molybdenum carbide mass proportions of the surface layer and the core layer are controlled, a hard phase enrichment area is formed on the surface layer, a binding phase enrichment area is formed on the inner core part, the Vickers hardness can be improved through hard phase enrichment, the fracture toughness can be improved through binding phase enrichment, and therefore the Ti (C, N)-based metal ceramic with the hardness and the fracture toughness is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of powder metallurgy, in particular to a gradient multilayer nano Ti (C, N) based cermet and a preparation method thereof. Background Art

[0002] Since WC and Co resources are scarce and very expensive, it is difficult to ensure the sustainable development of cemented carbide, so it is necessary to find alternative materials for WC-Co cemented carbide. The global reserves of titanium (Ti) are about 1,000 times that of tungsten. From the cost point of view, the production of Ti (C, N)-based composite materials is more profitable, so Ti (C, N)-based composite materials have huge market prospects. At the same time, Ti (C, N)-based ceramics have the advantages of high thermal hardness, good wear resistance, low friction coefficient, good chemical stability, etc., and are considered to be a substitute for WC-based cemented carbide.

[0003] Ti(C,N) based cermet is a composite material with ceramic hard phase and metal binder phase. It has both the plastic toughness of metal and the wear resistance of ceramic, which has attracted considerable research attention in the field of cutting tools and is often used as a cutting tool. However, due to its lower fracture strength and toughness than WC based cemented carbide, micro cracks are easily generated inside the material during processing, thus reducing its service life and hindering its widespread application. Summary of the invention

[0004] The present invention aims to provide a gradient multilayer nano Ti (C, N) based cermet and a preparation method thereof, so as to obtain a Ti (C, N) based cermet having both hardness and fracture toughness.

[0005] In order to achieve the above object, the specific scheme adopted by the present invention is: a method for preparing a gradient multilayer nano-Ti(C,N)-based cermet, comprising the following steps:

[0006] S1: According to mass percentage, 64.9% titanium carbonitride, 23% tungsten carbide, 8% cobalt, 4% molybdenum carbide and 0.1% graphene nanosheets are mixed to obtain powder I, and powder I is mixed with cemented carbide balls and anhydrous ethanol, and dried to obtain mixed powder I; 60.9% titanium carbonitride, 23% tungsten carbide, 8% cobalt, 8% molybdenum carbide and 0.1% graphene nanosheets are mixed to obtain powder II, and powder II is mixed with cemented carbide balls and anhydrous ethanol, and dried to obtain mixed powder II;

[0007] S2: Adding mixed powder I and mixed powder II into a mold layer by layer to obtain three layers of mixed powder with a surface layer of mixed powder II and a core layer of mixed powder I, and performing spark plasma sintering to obtain the gradient multilayer nano-Ti(C,N)-based cermet.

[0008] As a further optimization of the above technical solution: the particle size of titanium carbonitride is 0.5-0.8μm, the particle size of tungsten carbide is 180-220nm, the particle size of cobalt is 45-65nm, the particle size of molybdenum carbide is 1-3μm, and the sheet size of graphene nanosheets is 5-10μm.

[0009] As a further optimization of the above technical solution: in the three-layer mixed powder, the mass ratio of the single surface layer to the core layer is greater than or equal to 0.4 and less than or equal to 0.5.

[0010] As a further optimization of the above technical solution: powder I and powder II are mixed with carbide balls and anhydrous ethanol respectively by planetary ball milling or drum ball milling.

[0011] As a further optimization of the above technical solution: the rotation speed of the planetary ball mill or the drum ball mill is 180-240 rpm, and the mixing time is 16-20 hours.

[0012] As a further optimization of the above technical solution: in step S1, the drying temperature is 70-80°C and the drying time is 12-16h.

[0013] As a further optimization of the above technical solution: spark plasma sintering is carried out under vacuum conditions, using nitrogen as the protective gas, the sintering temperature is 1350-1500°C, the heat preservation and pressure holding time is 8-20min, and the sintering pressure is 30-45MPa.

[0014] As a further optimization of the above technical solution: the heating rate of spark plasma sintering is as follows: within 800°C, the heating rate is 50-60°C / min, 800°C-1500°C, the heating rate is 70-80°C / min.

[0015] As a further optimization of the above technical solution: the vacuum degree of the vacuum condition is ≤1×10 -1 Pa.

[0016] A gradient multilayer nano-Ti(C, N)-based metal ceramic is prepared by any of the above methods.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The present invention controls the different mass proportions of molybdenum carbide in the surface layer and the core layer to form a hard phase-enriched area in the surface layer and a bonding phase-enriched area in the inner core. The hard phase enrichment can improve the Vickers hardness, and the bonding phase enrichment can improve the fracture toughness, thereby obtaining a Ti(C, N)-based cermet with both hardness and fracture toughness. At the same time, the cermet is set as a three-layer structure to reduce stress concentration, and the interface between the layers can deflect cracks and hinder crack propagation.

[0019] The graphene nanosheets added in the present invention can not only improve the strength and toughness of the gradient multilayer nano-Ti(C,N)-based cermet as a whole, but also strengthen the connection between interfaces, effectively avoiding material failure caused by interface cracking.

[0020] Using nitrogen as the protective gas, on the one hand, protects the powder from oxidation caused by the active gas; on the other hand, the constant voltage pulse current loading method and the control of the heating rate at different stages are conducive to the enrichment of nitrogen on the surface, thereby promoting the formation of hard phase and improving the surface hardness. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The powder charging method in Example 1, Example 2 and Example 3;

[0022] Figure 2 This is a 30,000-fold scanning electron microscope image of the gradient Ti(C, N)-based cermet surface in Example 3;

[0023] Figure 3 This is a 30,000-fold scanning electron microscope image of a cross section of the gradient Ti(C,N)-based cermet in Example 3;

[0024] Figure 4 This is a 10,000-fold SEM image of the metal ceramic core layer in Example 3 (i.e., 4% molybdenum carbide addition);

[0025] Figure 5 This is a 10,000-fold SEM image of the metal ceramic surface layer in Example 3 (i.e., 8% molybdenum carbide addition). DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further elaborated in detail below in conjunction with specific embodiments. The parts of the present invention that are not described and disclosed in detail in the following embodiments should be understood as the prior art known or should be known to those skilled in the art.

[0027] The present invention discloses a method for preparing a gradient multilayer nano-Ti(C,N)-based cermet, comprising the following steps:

[0028] S1: According to mass percentage, 64.9% titanium carbonitride, 23% tungsten carbide, 8% cobalt, 4% molybdenum carbide and 0.1% graphene nanosheets are mixed to obtain powder I, and powder I is mixed with cemented carbide balls and anhydrous ethanol by planetary ball milling or drum ball milling at a speed of 180-240 rpm for 16-20 hours. After mixing, it is dried at a temperature of 70-80° C. for 12-16 hours to obtain mixed powder I;

[0029] 60.9% titanium carbonitride, 23% tungsten carbide, 8% cobalt, 8% molybdenum carbide and 0.1% graphene nanosheets are mixed to obtain powder II, and powder II is mixed with carbide balls and anhydrous ethanol by planetary ball milling or drum ball milling at a rotation speed of 180-240rpm for a mixing time of 16-20h. After mixing, the mixture is dried at a temperature of 70-80°C for 12-16h to obtain mixed powder II; wherein the particle size of titanium carbonitride is 0.5-0.8μm, the particle size of tungsten carbide is 180-220nm, the particle size of cobalt is 45-65nm, the particle size of molybdenum carbide is 1-3μm, and the particle size of graphene nanosheets is 5-10μm. During planetary ball milling or drum ball milling, the amount of anhydrous ethanol added is just enough to cover the powder and the carbide balls.

[0030] S2: Adding mixed powder I and mixed powder II into a mold layer by layer to obtain a three-layer mixed powder with a surface layer of mixed powder II and a core layer of mixed powder I. In the three-layer mixed powder, the mass ratio of the single surface layer to the core layer is greater than or equal to 0.4 and less than or equal to 0.5; spark plasma sintering the three-layer mixed powder to obtain the gradient multilayer nano-Ti(C,N)-based cermet. The spark plasma sintering is carried out under vacuum conditions, and the vacuum degree of the vacuum conditions is ≤1×10 -1 Pa, nitrogen is used as the protective gas, the sintering temperature is 1350-1500℃, the heat preservation and pressure holding time is 8-20min, and the sintering pressure is 30-45MPa. The heating rate of spark plasma sintering is as follows: within 800℃, the heating rate is 50-60℃ / min, 800℃-1500℃, the heating rate is 70-80℃ / min.

[0031] Example 1

[0032] (1) Preparation

[0033] Weigh 64.9% Ti(C,N)-23% WC-8% Co-4% Mo according to mass percentage 2 C-0.1% GNS, mixed to obtain powder I, put powder I, YG8 carbide ball and anhydrous ethanol into a carbide ball mill, mix at a speed of 180 rpm, mixing time 20 h, and dry in a drying oven at 70 ° C for 12 h to obtain mixed powder I; weigh 60.9% Ti (C, N) -23% WC -8% Co -8% Mo according to mass percentage 2C-0.1% GNS, mix to obtain powder II, put powder II, YG8 carbide ball and anhydrous ethanol into a carbide ball mill and mix at a rotation speed of 180 rpm for 20 hours, dry in a drying oven at 70°C for 12 hours to obtain mixed powder II; wherein the sizes of the raw materials in powder I and powder II are: the particle size of titanium carbonitride is 0.62 μm, the particle size of tungsten carbide is 200 nm, the particle size of cobalt is 50 nm, the particle size of molybdenum carbide is 1-3 μm, and the sheet size of graphene nanosheets is 5-10 μm.

[0034] (2) Loading

[0035] The dried mixed powder I and mixed powder II are added layer by layer into the graphite mold: 1) the order of addition is mixed powder II (surface layer) - mixed powder I (core layer) - mixed powder II (surface layer), and each time a layer is added, the powder is flattened using a powder tablet press at a pressure of 5 MPa; 2) the mass ratio of a single surface layer to the core layer is 0.4, that is, the mass ratio of surface layer: core layer: surface layer is 0.4:1:0.4.

[0036] (3) Sintering

[0037] After assembly, spark plasma sintering equipment was used to load constant voltage pulse current under vacuum conditions (≤1×10 -1 Pa) and nitrogen atmosphere. Within 800°C, the heating rate is 50°C / min, within 800°C-1400°C, the heating rate is 75°C / min, the temperature is raised to 1400°C for sintering, that is, the sintering temperature is 1400°C, the sintering pressure is 35MPa, and the holding time is 16min; after the holding is completed, the temperature is naturally lowered to finally obtain a gradient multilayer nano-Ti(C,N)-based cermet.

[0038] The surface Vickers hardness of the gradient multilayer nano-Ti(C,N)-based cermet prepared in this embodiment is 2106 kgf / mm 2 、2026.4kgf / mm 2 , fracture toughness is 9.8MPa·m 1 / 2 , 9.7MPa·m 1 / 2 ; Vickers hardness of the core is 1941.9kgf / mm 2 , fracture toughness is 10.5MPa·m 1 / 2 There are no obvious defects and pores on the surface of the specimen, no brittle fracture and cracks on the cross section, and the microstructure is uniform.

[0039] Example 2

[0040] (1) Preparation

[0041] Weigh 64.9% Ti(C,N)-23% WC-8% Co-4% Mo according to mass percentage 2C-0.1% GNS, mixed to obtain powder I, put powder I, YG8 carbide ball and anhydrous ethanol into a carbide ball mill, mix at a speed of 180 rpm, mixing time 20 h, and dry in a drying oven at 70 ° C for 12 h to obtain mixed powder I; weigh 60.9% Ti (C, N) -23% WC -8% Co -8% Mo according to mass percentage 2 C-0.1% GNS, mix to obtain powder II, put powder II, YG8 carbide ball and anhydrous ethanol into a carbide ball mill and mix at a rotation speed of 180 rpm for 20 hours, dry in a drying oven at 70°C for 12 hours to obtain mixed powder II; wherein the sizes of the raw materials in powder I and powder II are: the particle size of titanium carbonitride is 0.62 μm, the particle size of tungsten carbide is 200 nm, the particle size of cobalt is 50 nm, the particle size of molybdenum carbide is 1-3 μm, and the sheet size of graphene nanosheets is 5-10 μm.

[0042] (2) Loading

[0043] The dried mixed powder I and mixed powder II are added layer by layer into the graphite mold: 1) the order of addition is mixed powder II (surface layer) - mixed powder I (core layer) - mixed powder II (surface layer), and each time a layer is added, the powder is flattened using a powder tablet press at a pressure of 5 MPa; 2) the mass ratio of a single surface layer to the core layer is 0.41, that is, the mass ratio of surface layer: core layer: surface layer is 0.41:1:0.41.

[0044] (3) Sintering

[0045] After assembly, spark plasma sintering equipment was used to load constant voltage pulse current under vacuum conditions (≤1×10 -1 Pa) and nitrogen atmosphere. Within 800°C, the heating rate is 50°C / min, and within 800°C-1400°C, the heating rate is 75°C / min. The temperature is raised to 1400°C for sintering, that is, the sintering temperature is 1400°C, the sintering pressure is 35MPa, and the insulation time is 8min; after the insulation is completed, the temperature is naturally lowered to finally obtain a gradient multilayer nano-Ti(C,N)-based cermet.

[0046] The surface Vickers hardness of the gradient multilayer nano-Ti(C,N)-based cermet prepared in this embodiment is 1921 kgf / mm 2 、2021kgf / mm 2 , fracture toughness is 8.27MPa·m 1 / 2 、8.7MPa·m 1 / 2 ; Vickers hardness of the core is 1880kgf / mm 2 , fracture toughness is 10.7MPa·m 1 / 2There are no obvious defects and pores on the surface of the sample, the microstructure is uniform, and there are more black hard phases; there is no brittle fracture and cracks on the cross section, the microstructure is uniform, and there are more gray bonding phases.

[0047] Example 3

[0048] (1) Preparation

[0049] Weigh 64.9% Ti(C,N)-23% WC-8% Co-4% Mo according to mass percentage 2 C-0.1% GNS, mixed to obtain powder I, put powder I, YG8 carbide ball and anhydrous ethanol into a carbide ball mill, mix at a speed of 180 rpm, mixing time 20 h, and dry in a drying oven at 70 ° C for 12 h to obtain mixed powder I; weigh 60.9% Ti (C, N) -23% WC -8% Co -8% Mo according to mass percentage 2 C-0.1% GNS, mix to obtain powder II, put powder II, YG8 carbide ball and anhydrous ethanol into a carbide ball mill and mix at a rotation speed of 180 rpm for 20 hours, dry in a drying oven at 70°C for 12 hours to obtain mixed powder II; wherein the sizes of the raw materials in powder I and powder II are: the particle size of titanium carbonitride is 0.62 μm, the particle size of tungsten carbide is 200 nm, the particle size of cobalt is 50 nm, the particle size of molybdenum carbide is 1-3 μm, and the sheet size of graphene nanosheets is 5-10 μm.

[0050] (2) Loading

[0051] The dried mixed powder I and mixed powder II are added layer by layer into the graphite mold: 1) the order of addition is mixed powder II (surface layer) - mixed powder I (core layer) mixed powder II (surface layer), and each time a layer is added, the powder is flattened using a powder tablet press at a pressure of 5 MPa; 2) the mass ratio of a single surface layer to a core layer is 0.42, that is, the mass ratio of surface layer: core layer: surface layer is 0.42:1:0.42.

[0052] (3) Sintering

[0053] After assembly, spark plasma sintering equipment was used to load constant voltage pulse current under vacuum conditions (≤1×10 -1 Pa) and nitrogen atmosphere. Within 800°C, the heating rate is 50°C / min, within 800°C-1400°C, the heating rate is 75°C / min, the temperature is raised to 1400°C for sintering, that is, the sintering temperature is 1400°C, the sintering pressure is 45MPa, and the holding time is 8min; after the holding is completed, the temperature is naturally lowered to finally obtain a gradient multilayer nano-Ti(C,N)-based cermet.

[0054] The surface Vickers hardness of the gradient multilayer nano-Ti(C,N)-based cermet prepared in this embodiment is 1998 kgf / mm 2 、2050kgf / mm 2 , fracture toughness is 9.28MPa·m 1 / 2 、9.55MPa·m 1 / 2 ; Vickers hardness of the core is 1920kgf / mm 2 , fracture toughness is 11.1MPa·m 1 / 2 There are no obvious defects and pores on the surface of the sample, the microstructure is uniform, and there are more black hard phases; there is no brittle fracture and cracks on the cross section, the microstructure is uniform, and there are more gray bonding phases.

[0055] Comparative experiment 1

[0056] Weigh 65% Ti(C,N)-23% WC-8% Co-4% Mo according to mass percentage 2 C, mixed; wherein the particle size of titanium carbonitride is 0.62μm, the particle size of tungsten carbide is 200nm, the particle size of cobalt is 50nm, and the particle size of molybdenum carbide is 1-3μm.

[0057] The weighed powder, YG8 carbide ball (ball-to-material ratio 8:1) and anhydrous ethanol were placed in a carbide ball mill and mixed for 20 hours. Dry in a drying oven at 70°C for 12 hours. The dried mixture was placed in a graphite mold and sintered in a nitrogen atmosphere using a spark plasma sintering device with a constant voltage pulse current loading method.

[0058] The sintering pressure is 35MPa, the holding time is 16min, and the sintering temperature is 1400℃; within 800℃, the heating rate is 50℃ / min, within 800℃-1400℃, the heating rate is 75℃ / min, and after the holding is completed, the temperature is naturally lowered to finally obtain Ti(C,N)-based metal ceramics.

[0059] The Vickers hardness of the Ti(C,N)-based cermet prepared by this method is 1929kgf / mm 2 , fracture toughness is 9MPa·m 1 / 2 The sample has fine grains and few defects.

[0060] Comparative experiment 2

[0061] Weigh 64.9% Ti(C,N)-23% WC-8% Co-4% Mo according to mass percentage 2 C-0.1% GNS, the sizes of the raw materials are: the particle size of titanium carbonitride is 0.62 μm, the particle size of tungsten carbide is 200 nm, the particle size of cobalt is 50 nm, the particle size of molybdenum carbide is 1-3 μm, and the sheet size of graphene nanosheets is 5-10 μm.

[0062] The weighed powder, YG8 carbide ball (ball-to-material ratio 8:1) and anhydrous ethanol were placed in a carbide ball mill and mixed for 20 hours. The mixture was dried in a drying oven at 70°C for 12 hours. The dried mixture was placed in a graphite mold and subjected to constant voltage pulse current loading under vacuum conditions (≤1×10 -1 Pa) for sintering. The sintering pressure is 35MPa, the holding time is 16min, and the sintering temperature is 1400℃; within 800℃, the heating rate is 50℃ / min, within 800℃-1400℃, the heating rate is 75℃ / min, the holding is completed, the temperature is naturally lowered, and finally the Ti(C,N)-based metal ceramic is obtained. The Vickers hardness of the Ti(C,N)-based metal ceramic prepared by this method is 1918kgf / mm 2 , fracture toughness is 10.1MPa·m 1 / 2 The sample has fine grains and few defects.

[0063] Result analysis:

[0064] Compared with Example 3, the difference between Comparative Experiment 1 and Example 3 is that no gradient metal ceramic is prepared, no graphene nanosheets are added, and the raw material of the metal ceramic prepared in Comparative Experiment 1 contains Mo. 2 The mass percentage of C is 4%. Compared with the core layer of Example 1, the Vickers hardness and fracture toughness are reduced. Among them, the fracture toughness of Example 3 is improved by 23% compared with that of Comparative Experiment 1.

[0065] The difference between Comparative Experiment 2 and Example 3 is that no gradient metal ceramic is prepared, and the raw material of the metal ceramic prepared in Comparative Experiment 2 contains Mo. 2 The mass percentage of C is 4%. Compared with Example 3, Example 3 forms a gradient structure, that is, the surface hardness is increased by 7% compared with Test 2, and the core fracture toughness is increased by 10% compared with Test 2, and the sample has better strength.

[0066] Figure 4 This is a 10,000-fold SEM image of the metal ceramic core layer in Example 3 (i.e., 4% molybdenum carbide addition). Figure 5 This is a 10,000-fold SEM image of the metal ceramic surface layer in Example 3 (i.e., 8% molybdenum carbide addition). Figure 4 It can be seen that when the addition amount of molybdenum carbide is 4%, the gray phase is more and the black hard phase is moderate in the metal ceramic sample. Figure 5 , the black hard phase is enriched and the gray bonding phase is less, so it can be inferred that when 8% molybdenum carbide is added, the metal ceramic has better hardness; when 4% molybdenum carbide is added, the metal ceramic has better strength and toughness.

[0067] The formation process of (Ti,Mo,W,)(C,N) annular phase during sintering is as follows:

[0068]

[0069] It can be seen that the more molybdenum carbide is added, the more annular phases are formed. In addition, the addition of molybdenum carbide can effectively prevent the dissolution of WC and Ti (C, N) in Co, thereby inhibiting the dissolution and grain growth of Ti (C, N) during sintering, achieving the effect of refining the grain size and improving the density of the metal ceramic sample. 2 The presence of C allows the molybdenum-rich phase to surround the hard phase, which can prevent the Ti(C,N) particles from approaching and contacting each other and reduce the growth of carbide particles.

[0070] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a gradient multilayer nano-Ti(C,N)-based cermet, characterized in that: The following steps are involved: S1: According to mass percentage, 64.9% titanium carbonitride, 23% tungsten carbide, 8% cobalt, 4% molybdenum carbide and 0.1% graphene nanosheets are mixed to obtain powder I, and powder I is mixed with cemented carbide balls and anhydrous ethanol, and dried to obtain mixed powder I; 60.9% titanium carbonitride, 23% tungsten carbide, 8% cobalt, 8% molybdenum carbide and 0.1% graphene nanosheets are mixed to obtain powder II, and powder II is mixed with cemented carbide balls and anhydrous ethanol, and dried to obtain mixed powder II; S2: Adding mixed powder I and mixed powder II into a mold layer by layer to obtain three layers of mixed powder with a surface layer of mixed powder II and a core layer of mixed powder I, and performing spark plasma sintering to obtain the gradient multilayer nano-Ti(C,N)-based cermet.

2. The method for preparing a gradient multilayer nano-Ti(C,N)-based cermet according to claim 1, characterized in that: The particle size of titanium carbonitride is 0.5-0.8 μm, the particle size of tungsten carbide is 180-220 nm, the particle size of cobalt is 45-65 nm, the particle size of molybdenum carbide is 1-3 μm, and the sheet size of graphene nanosheets is 5-10 μm.

3. The method for preparing a gradient multilayer nano-Ti(C,N)-based cermet according to claim 1, characterized in that: In the three-layer mixed powder, the mass ratio of the single surface layer to the core layer is greater than or equal to 0.4 and less than or equal to 0.

5.

4. The method for preparing a gradient multilayer nano-Ti(C,N)-based cermet according to claim 1, characterized in that: The powders I and II are respectively mixed with carbide balls and anhydrous ethanol by planetary ball milling or drum ball milling.

5. The method for preparing a gradient multilayer nano-Ti(C,N)-based cermet according to claim 4, characterized in that: The rotation speed of the planetary ball mill or the drum ball mill is 180-240 rpm, and the mixing time is 16-20 h.

6. The method for preparing a gradient multilayer nano-Ti(C,N)-based cermet according to claim 1, characterized in that: In step S1, the drying temperature is 70-80°C and the drying time is 12-16 hours.

7. The method for preparing a gradient multilayer nano-Ti(C,N)-based cermet according to claim 1, characterized in that: Spark plasma sintering is carried out under vacuum conditions, using nitrogen as the protective gas, the sintering temperature is 1350-1500°C, the heat preservation and pressure holding time is 8-20min, and the sintering pressure is 30-45MPa.

8. The method for preparing a gradient multilayer nano-Ti(C,N)-based cermet according to claim 7, characterized in that: The heating rate of spark plasma sintering is as follows: within 800°C, the heating rate is 50-60°C / min, 800°C-1500°C, the heating rate is 70-80°C / min.

9. The method for preparing a gradient multilayer nano-Ti(C,N)-based cermet according to claim 7, characterized in that: The vacuum degree of vacuum condition is ≤1×10 -1 Pa.

10. A gradient multilayer nano-Ti(C,N)-based cermet, characterized in that: Prepared by the method described in any one of claims 1 to 9.

Citation Information

Cited By

  • Multi-region gradient hard alloy material and preparation method thereof

    CN120758775A

  • Titanium-based metal ceramic, preparation method thereof and cutting tool

    CN120830035A